Peranan Komitmen Organisasi dan Employee Engagement terhadap Kesiapan Karyawan untuk Berubah - Zulkarnain Zulkarnain; Sherry Hadiyani (Faculty of Psychology, Universitas Gadjah Mada, 2014)
This study had two objectives, the first was to find out the role of organizational commitment and employee engagement to readiness for change. Second was to find out the determinants of readiness for change based on aspects of organizational commitment (i.e., identification, involvement, and loyalty) and dimensions of employee engagement (i.e., organization, leadership, team member, job and individual). Self-administered questionnaires were used to measure the three variables. There were 206 plantation employees involved in this study. The result showed that organizational commitment and employee engagement contributed to employee readiness for change. This study also found two aspects of organizational commitment and two dimensions of employee engagement contributing to employee readiness for change. This study could be the guidelines for the policy makers in implementing policies of better human resources. Keywords: organizational commitment, employee engagement, readiness for change, plantation employees, human resource